Endometrial curettage in abnormal vaginal bleedings in 1964 and 1983 at the Panti Rapih Hospital, Yogyakarta, and family planning - Roekmini Soedibjo Roekmini Soedibjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1984)
This study was undertaken to compare the causes of abnormal vaginal bleedings in 1964 before the family planning program in Indonesia was introduced and in 1983 when this program was widely accepted:The samples were taken from the files of the Department of Pathology, Gadjah Mada University Medical Faculty, during the period of July 1 — December 31 in the years 1964 and 1983.The results suggested that in 1964 these bleedings were mainly caused by conception (52.9%), while in 1983 only 19.7% were caused by conception. In 1964 most dysfunctional bleedings were found in the perimenopause groups and in 1983 in the child bearing groups.Extended studies utilizing larger samples could provide further information about the role of ex - ogen hormons for contraception and therapy or hormons for cosmetic purposes, and also about endogenic factors; it would be necessary to work together with other specialists as well as psychologists.Key Words: abnormal vaginal bleeding - endometrial curettage - family planning program